The 11th Presidential Election in Iran - Kamal, Abdol Moghset Bani; Gamshadzehifar, Hadi (Universiti Kebangsaan Malaysia, 2014)
The political structure of Iran is a theocratic system based on Shia doctrine. The most powerful religious and political authority is a Shia religious authority known as the Supreme Leader. However, the head of government is a president elected through popular vote. So far eleven presidential elections have been held since the 1979 revolution. The eleventh presidential election was held on June 14, 2013. It was one of the most important presidential elections. It owed its importance to the previous controversial presidential election in 2009 which led to a wide popular uprising. More importantly, the eleventh presidential election was held amid tensions among different political streams within the political system. Based on primary and some secondary sources, this paper looks at the Iranian electoral laws, the candidates, their campaigns, voting, the election result and the wider significance of the eleventh presidential election. It specifically answers the following questions: what was the importance of the eleventh presidential election? What were the electoral laws, institutions and procedures for the presidential election in Iran? How was the presidential election conducted? What role do presidential elections play in the Iranians’ quest for democracy? This paper finds that although the election results received welcome by Iranians, there are significant flaws in the Iranian electoral system which casts doubt on the credibility of the elections being held in Iran. In particular, there were series of events during the eleventh presidential election which affected its natural outcome. Finally, this paper discovers that despite the conservatives’ paean, the presidential election was a major setback for them.